Preoperative Anti–tumor Necrosis Factor Therapy in Patients with Ulcerative Colitis Is Not Associated with an Increased Risk of Infectious and Noninfectious Complications After Ileal Pouch–anal Anastomosis. Issue 10 (October 2016) - Zittan, Eran; Milgrom, Raquel; Ma, Grace W.; Wong-Chong, Nathalie; O'Connor, Brenda; McLeod, Robin S.; MacRae, Helen M.; Greenberg, Gordon R.; Nguyen, Geoffrey C.; Croitoru, Kenneth; Steinhart, A. Hillary; Cohen, Zane; et al.
Abstract : Background: There are conflicting data regarding the effect of previous exposure to anti–tumor necrosis factor (anti-TNF) therapy on complication rates after pelvic pouch surgery for patients with ulcerative colitis (UC). In particular, there is concern surrounding the rates of pouch leaks and infectious complications, including pelvic abscesses, in anti–TNF-treated subjects who require ileal pouch–anal anastomosis (IPAA) surgery. Methods: A retrospective study was performed in UC subjects who underwent IPAA between 2002 and 2013. Demographic data, clinical data, use of anti-TNF therapy, steroids, immunosuppressants, and surgical outcomes were assessed. Results: Seven hundred seventy-three patients with UC/IPAA were reviewed. Fifteen patients were excluded from the analysis because of missing data. There were 196 patients who were exposed to anti-TNF therapy and 562 patients who were not exposed to anti-TNF therapy preoperatively. There were no significant differences in the postoperative IPAA leak rate between those exposed to anti-TNF therapy and the control group (n = 26 [13.2%] versus 66 [11.7%], respectively, P = 0.44). In addition, there were no significant differences in the postoperative 2-stage IPAA leak rate in those who had been operated on within 15 days from the last anti-TNF dose (n = 10), within 15 to 30 days (n = 17), or 31 to 180 days (n = 54) (10%, 5.9%, and 14.8% respectively, P = 0.43) nor were there differences based on the presence of detectable infliximab serum levels. Conclusions: Preoperative anti-TNF therapy in patients with UC is not associated with an increased risk of infectious and noninfectious complications after IPAA including pelvic abscesses, leaks, and wound infections. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 8 September 2016.